2017
DOI: 10.1080/10409238.2016.1276882
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs: a regulator of cellular stress

Abstract: Circular RNAs (CircRNAs) were first identified as a viroid and later found to also be an endogenous RNA splicing product in eukaryotes. In recent years, a series of RNA-sequencing analyses from a diverse range of eukaryotes have shed new light on these eukaryotic circRNAs, revealing dynamic expression patterns in various developmental stages and physiological conditions. In this review, we focus on circRNAs implicated in stress response pathways and explore potential mechanisms underlying their regulation. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
131
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 104 publications
1
131
1
Order By: Relevance
“…CircRNAs have been postulated to function as microRNA sponges (Hansen et al, 2013, 2011; Memczak et al, 2013), in cell-to-cell information transfer (Lasda and Parker, 2016), as templates for translation (Legnini et al, 2017; Pamudurti et al, 2017; Yang et al, 2017), or memory due to their extraordinary stability (Fischer and Leung, 2017). However, the ability of exogenous circRNA to activate immune response or inhibit viral infection has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs have been postulated to function as microRNA sponges (Hansen et al, 2013, 2011; Memczak et al, 2013), in cell-to-cell information transfer (Lasda and Parker, 2016), as templates for translation (Legnini et al, 2017; Pamudurti et al, 2017; Yang et al, 2017), or memory due to their extraordinary stability (Fischer and Leung, 2017). However, the ability of exogenous circRNA to activate immune response or inhibit viral infection has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are generally considerate as non-coding RNA, although Pamudurti et al found some specific circRNAs can also transcribed into proteins [7]. Increasing evidence reveals that circRNAs have key functions in regulating various physiological and pathological processes [8, 9]. It has been demonstrated that circRNAs could serve as competing endogenous RNAs (ceRNAs) to inhibit the activity of microRNAs (miRNAs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…But recently, mounting studies have shown that circRNAs play important roles and serve various functions in nervous system, carcinogenesis, cardiovascular diseases, immunomodulation and metabolic disorder [5][6][7][8]. CircRNA could regulates target gene or protein expression in various manners [9]: function as microRNA (miRNA) sponges to show miRNA inhibition effect by competing endogenous RNA (ceRNA) [10], interfere with their parental genes by modulation of alternative splicing or transcription [11], and interact with RNA-binding proteins (RBPs) as scaffolds for the assembly of protein complexes [12].…”
Section: Introductionmentioning
confidence: 99%